A Nomogram Model Containing Genetic Polymorphisms to Predict Risk of Pulmonary Embolism in Pregnant Women - Sun H; Zhou L; Lu Y; Li Y; Huo Y; Huang W (Dove Medical Press, 2024)
Huiqin Sun,1,* Lu Zhou,2,* Yihan Lu,2 Yingchuan Li,3 Yan Huo,4 Weifeng Huang5 1Department of Anesthesiology, Shanghai Sixth People’s Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China; 2Department of Epidemiology, Ministry of Education Key Laboratory of Public Health Safety, School of Public Health, Fudan University, Shanghai, People’s Republic of China; 3Department of Critical Care Medicine, Tongji University Affiliated Shanghai Tenth People’s Hospital, Shanghai, People’s Republic of China; 4Department of Pharmacy, Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090 People’s Republic of China; 5Department of Critical Care Medicine, Shanghai Xuhui Central Hospital, Zhongshan-Xuhui Hospital, Fudan University, Fudan, 200031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Weifeng Huang, Department of Critical Care Medicine, Shanghai Xuhui Central Hospital, Zhongshan-Xuhui Hospital, Fudan University, 366 NorthLongchuan Rd, Xuhui District, Shanghai, 200031, People’s Republic of China, Email breeze-huang@hotmail.com Yan Huo, Department of Pharmacy, Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of China, Email huoyan@sjtu.edu.cnIntroduction: Pulmonary embolism (PE), the most serious presentation of venous thromboembolism (VTE), is associated with a high rate of mortality and expense. Clinical studies on pregnant women with PE are scarce. The aim of this study was to analyze the clinical impact of fibrinolytic enzyme activation inhibitor-1 (PAI-1) 4G/5G genetic polymorphisms, methylenetetrahydrofolate reductase (MTHFR) rs1801131 (A1298C) and rs1801133 (C677T) genetic polymorphisms, and establish a predictive model for pregnant women.Material and Methods: Between September 2022 and August 2023, 53 pregnant women with PE were enrolled. Using the propensity score matching method, 106 consecutive pregnant women without VTE were 1:2 matched. The relevant patient data were collected, and the susceptibility genes for PE were detected to determine genetic polymorphisms, and PE susceptibility in pregnant women, as well as to develop predictive models.Results: Our study showed that 4G/4G homozygous mutations increased the risk of pregnant PE fourfold (OR = 4.46, 95% CI = 1.59– 12.50, P = 0.004), whereas the 4G allele mutation increased the risk twofold (OR = 2.33, 95% CI = 1.35– 4.04, P = 0.002). A nomogram was established to predict the risk of pregnant women with PE by four predictive features including PAI-1 genetic polymorphisms, international normalized ratio (INR), antithrombin-III (AT-III) activity, and platelet count (PLT). The area under the curve (AUC) of the nomogram was 0.821 (0.744– 0.898). The AUC of the internal validation group was 0.822 (0.674– 0.971). Decision curve analysis revealed that the nomogram has a higher net benefit in the following threshold: probability interval of ≥ 15%.Conclusion: The PAI-1 4G/4G genotype is an independent risk factor for pregnant women with PE; furthermore, the presence of the 4G allele can increase the risk of PE. The study established a nomogram to predict the risk of PE in pregnant women.Keywords: pulmonary embolism, pregnant women, genetic polymorphisms, PAI-1, nomogram model